The combustion and emission characteristics of a common-rail diesel engine fueled with diesel, propanol, and pentanol blends under low intake pressures. (1st January 2022) - Zhao, Weihua; Yan, Junhao; Gao, Suya; Lee, Timothy H.; Li, Xiangrong
Highlights: Engine performance of diesel/propanol and diesel/pentanol blends were investigated. The effects of low intake pressure on engine performance were studied. Pe20 and Pe40 can extend operating range of diesel engines at low intake pressure. Diesel alcohol blends show fewer CO, HC, and soot emissions. Pentanol/diesel blends have similar or higher ITE than diesel at low intake pressure. Abstract: Due to the expansion of the global population and rapid economic growth, human activities at high-altitude regions are expected to grow. However, diesel engines are the main power sources for heavy-duty machinery, which can experience low combustion efficiency and high emissions due to the reduction of intake air mass. Adopting oxygenated fuels, such as alcohols, can be a possible solution to overcome these issues. Therefore, the study of the performance and emission characteristics of diesel engines fueled with diesel/alcohol blends under high-altitude conditions are necessary. To investigate the effects of low intake pressure and alcohol additives on the performance of diesel engines, the combustion and emission characteristics of a common-rail diesel engine fueled with diesel, propanol, and pentanol blends under different intake pressures were tested. Five intake pressures (1.2, 1.0, 0.8, 0.7 and 0.6 atm) were selected in this work. Propanol and pentanol (20% and 40% by volume) were added into diesel to achieve blends of Pr20, Pr40, Pe20, and Pe40. As compared to diesel, diesel/propanol and diesel/pentanol blends had longer ignition delays and shorter combustion durations. This means Pe20 and Pe40 can extend the operating range of diesel engines under low intake pressure conditions. Diesel/alcohol blends had higher NOx emissions but reduced soot emissions compared to pure diesel. With the same blend content, a higher blend ratio resulted in increased NOx emissions and lower soot emissions. The CO emissions of the tested fuels remained low (about 3 g/kWh) under higher intake pressures, while increasing dramatically when the intake pressure was lower than 0.8 atm. The HC emissions of the tested fuels also stayed low (around 0.2 g/kWh) when the intake pressure was over 0.7 atm.